A sink-specific H+/monosaccharide co-transporter from Nicotiana tabacum: cloning and heterologous expression in baker's yeast. - Sauer, Norbert; Stadler, Ruth (Plant Journal, 1993)
A cDNA clone for a monosaccharide transporter (MST1) was isolated from tobacco, which is most strongly expressed in the various sink tissues of mature tobacco plants: roots, flowers, and young leaves. An open reading frame of 1569 bp codes for a protein with 523 amino acids and a calculated molecular weight of 57,717 Da. The protein is homologous to a group of other plant monosaccharide transport proteins from Arabidopsis thaliana and Chlorella kessleri, to human glucose transporters and to Saccharomyces cerevisiae and several bacterial sugar transport proteins. As with these other transporters, the MST1 protein is extremely lipophilic and has 12-putative membrane-spanning domains. Heterologous expression of the MST1 cDNA clone in Saccharomyces cerevisiae allowed its characterization as a putative H+/monosaccharide co-transporter, catalyzing the uptake of hexoses (e.g. D-glucose and D-galactose) or pentoses (e.g. D-xylose) and the energy dependent and uncoupler sensitive accumulation of non-metabolizable substrates (e.g. D-xylose or 3-O-methyl-glucose). Polyclonal antibodies were raised against a fusion protein of beta-galactosidase and the last 27 amino acids of the C-terminus of the MST1 protein. In SDS extracts of transformed yeast cells these antibodies recognize a polypeptide with an apparent molecular weight of 42 kDa, which is absent in extracts from untransformed control cells.